Evolving perspectives on evaluating obesity: from traditional methods to cutting-edge techniques - Heyue Wang; Yaxin Qin; Jinzhu Niu; Haowen Chen; Xinda Lu; Rui Wang; Jianli Han (Annals of Medicine)
Objective: This review examines the evolution of obesity evaluation methods, from traditional anthropometric indices to advanced imaging techniques, focusing on their clinical utility, limitations, and potential for personalized assessment of visceral adiposity and associated metabolic risks.Methods: A comprehensive analysis of existing literature was conducted, encompassing anthropometric indices (BMI, WC, WHR, WHtR, NC), lipid-related metrics (LAP, VAI, CVAI, mBMI), and imaging technologies (3D scanning, BIA, ultrasound, DXA, CT, MRI). The study highlights the biological roles of white, brown, and beige adipocytes, emphasizing visceral adipose tissue (VAT) as a critical mediator of metabolic diseases.Conclusion: Although BMI and other anthropometric measurements are still included in the guidelines, indicators that incorporate lipid metabolism information can more accurately reflect the relationship between metabolic diseases and visceral obesity. At the same time, the use of more modern medical equipment, such as ultrasound, X-rays, and CT scans, allows for a more intuitive assessment of the extent of visceral obesity.